Pengaruh Cyber Crime dan Cyber Security Terhadap Tingkat Kepercayaan Nasabah Bank Syariah Dalam Menggunakan Layanan M-banking di Wilayah Surabaya - Febriana, Vivi Cendrik; Indrarini, Rachma (Jurnal Ekonomika dan Bisnis Islam, 2024)
This research aims to determine the influence of cyber crime and cyber security on the level of trust of sharia bank customers in using m-banking services in the Surabaya area. The research method used is a quantitative method with an associative approach and sampling was taken using purposive sampling. This research uses primary data involving 120 samples. The results of this research show that 1) cyber crime influences the trust of sharia bank customers in using m-banking services in the Surabaya area, 2) cyber security influences the trust of sharia bank customers in using m-banking services in the Surabaya area, and 3) Cyber crime and cyber security jointly influence the level of trust of sharia bank customers in using m-banking services in the Surabaya area. With this influence, it is important for customers to be more vigilant in using m-banking services that will be accessed in public places and for banks to always strengthen, update and carry out regular checks regarding security systems, especially in the field of internet technology.